2021
DOI: 10.1007/s11869-021-01006-w
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-city comparisons of PM2.5 concentration changes under COVID-19 social distancing in seven major cities of South Korea

Abstract: The COVID-19 pandemic has prompted governments around the world to impose mitigation strategies of unprecedented scales, typically involving some form of restrictions on social activities and transportation. The South Korean government has been recommending a collection of guidelines now known as social distancing, leading to reduced human activities. This study analyzes changes in the concentrations of fine particulate matter (PM2.5) during the 30-day periods before and since the start of social distancing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…China initiated a full lockdown in late January to early February, while other regions experienced partial or full lockdowns from April to May [31]. While Sokhi et al [31] comprehensively analyzed the global data and reported a decrease of approximately 30% to 40% in mean PM2.5 concentrations during the 2020 full lockdown compared to the same period in 2015-2019, several studies conducted in East Asia showed more complex PM2.5 signals [27,28,29,30,32,52,53]. Literature also reports reductions in PM2.5 levels over outflow regions during the COVID-19 period [9,24,28,29,31,32].…”
Section: Covid-19 Restrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…China initiated a full lockdown in late January to early February, while other regions experienced partial or full lockdowns from April to May [31]. While Sokhi et al [31] comprehensively analyzed the global data and reported a decrease of approximately 30% to 40% in mean PM2.5 concentrations during the 2020 full lockdown compared to the same period in 2015-2019, several studies conducted in East Asia showed more complex PM2.5 signals [27,28,29,30,32,52,53]. Literature also reports reductions in PM2.5 levels over outflow regions during the COVID-19 period [9,24,28,29,31,32].…”
Section: Covid-19 Restrictionmentioning
confidence: 99%
“…While Sokhi et al [31] comprehensively analyzed the global data and reported a decrease of approximately 30% to 40% in mean PM2.5 concentrations during the 2020 full lockdown compared to the same period in 2015-2019, several studies conducted in East Asia showed more complex PM2.5 signals [27,28,29,30,32,52,53]. Literature also reports reductions in PM2.5 levels over outflow regions during the COVID-19 period [9,24,28,29,31,32]. Some studies have observed a rebound in PM2.5 levels in South Korea and the Pearl River Delta following the easing of COVID-19 restrictions [28,32], while other has reported continued reductions in PM2.5 levels in Japan in 2021 [9].…”
Section: Covid-19 Restrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the decrease of air pollutants concentration has been negligible since 2015 (Lee et al 2021 ), the concentration of particulate matter (PM) with diameters ≤ 2.5 μm (PM 2.5 ) was found to have decreased significantly from the 2019 winter to the 2021 (NIER 2021 ; posts dated January 10, 2022, in the press release on http://eng.me.go.kr/ ). The large reduction in the PM 2.5 was most likely due to the social distancing precautions that were taken during the coronavirus disease (COVID-19) pandemic period; when COVID-19 protocols subsided, PM 2.5 returned to the previous concentrations (Ju et al 2021 ; Kwak et al 2021 ). This is a great concern for the public health in Korea which has suffered from the phenomenon ‘ Sam-Han-Sa-Mi ’, which translates to the alternation between three cold and four polluted days.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19로 인한 사람들의 활동 변화는 대기 중 PM 2.5 를 포함한 대기오염물질의 농도 변화를 야기할 수 있으며, 10,11) 이 러한 농도 변화는 노출양상의 변화를 가져올 가능성이 있다.…”
unclassified